MENINGKATKAN KEMAMPUAN ANAK AUTISME DALAM BIDANG BANTU DIRI MANDI DENGAN METODE PECS DI WISMA RASIDA 15A - Nini, Klemensia; Ndamung Maramba, Abed Nego (Jurnal Pelayanan Pastoral, 2022)
This study aims to find out how much influence the PECS (Picture Exchange Communication System) method has on the ability to help bathe in children with autism disorders. The research design used is the SSR (Single Subject Research) A-B-A design for 12 sessions. The results of the study focused on ten indicators of bath self-help exercises: 1) taking toiletries, 2) bringing toiletries to the bathroom, 3) putting toiletries in place, 4) taking water in buckets with dippers, 5) watering the body with water 4 to 5 times, 6) taking and wetting soap, 7) rubbing soap on the face, neck, and back of the ears, 8) rubbing soap on the left and right arms to the tips of the fingers and armpits, body and back, both feet and fingers, 9) rinse the whole body clean, 10) dry the body with a towel starting from the hair, face, neck, ears, arms and armpits, body, back, and legs, to dry. The results showed that the baseline-1 (A) phase was carried out for 3 sessions obtaining an average score of 36%, the intervention phase (B) was carried out for 6 sessions with an average score of 76.6%, and the baseline-2 (A) phase was carried out for 3 sessions with an average score of 80%. The results of visual analysis in conditions show that the directional tendency increases from session to session which means that it shows a good change (+). While in the analysis between conditions the level change from the baseline phase to the intervention phase increased from the previous data while the percentage overlap in phases A1 and B was 0%; Phases A2 and B by 0.3%. The conclusion that can be drawn is that changes in the ability to help themselves bathe in children with autism occur due to the intervention of the PECS method